Effect of Formulations and Sweetener Type to Characteristic of Coconut-Pineapple Isotonic Drink - Aprilia, Ayu; Maherawati, Maherawati; Dewi, Yohana S K (Universitas Pattimura, 2023)
Isotonic drinks can replace body fluids quickly because they contain electrolytes needed by the body. This study uses young coconut water as the primary raw material with the addition of pineapple juice to improve the taste and nutritional value of isotonic drinks. This study aimed to determine the characteristics of coconut water isotonic drinks by adding pineapple juice with different formulations and sweeteners. This study used a factorial block randomized experimental design consisting of two factors; the concentration of fruit juice and variations in the type of sweetener. The total of coconut water and pineapple juice was 20 mL with the ratio of coconut water: pineapple juice (14:6); (10:10); and (6:14). The sweeteners used were sucrose (6 g), honey (0.4 g), and stevia (0.03 g). The results showed that the different formulations of coconut-pineapple water affected the antioxidant activity, total dissolved solids, and potassium content of the coconut-pineapple water isotonic drink. Different sweeteners affected the antioxidant activity and total soluble solids of pineapple coconut water isotonic drink. The interaction of formulation and type of sweetener affected antioxidant activity and potassium content. The coconut-pineapple water isotonic drink in this study has met the SNI for isotonic drinks in pH values, sodium content, and total soluble solids for sucrose and stevia sweeteners, but the potassium content still exceeds the standards set by the SNI.